2022
DOI: 10.1177/15248399221115063
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated and Experienced Stigma After Testing Positive for SARS-CoV-2: A Qualitative Study

Abstract: Introduction Stigma has inhibited public health practitioners’ influence during the COVID-19 pandemic. We explore the experienced and anticipated stigma of people affiliated with a large university in the United States, using the Health Stigma and Discrimination Framework. Methods We conducted a qualitative secondary substudy of 20 people who tested SARS-CoV-2 positive and 10 who tested negative in the summer of 2020, selected from a study of 3,324 university students and employees. Findings No participants re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The most common was social isolation. 16,17,1921,3335,37,39,41,42,44,47,48,53,56,57,60,73,76,88 In 16 studies blaming from others was the second most common social stigma reported due to being infected with COVID-19. 22,23,39,40,46,48,5155,60,62,72,83,89 In 13 studies, participants experienced rejection from the social environment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most common was social isolation. 16,17,1921,3335,37,39,41,42,44,47,48,53,56,57,60,73,76,88 In 16 studies blaming from others was the second most common social stigma reported due to being infected with COVID-19. 22,23,39,40,46,48,5155,60,62,72,83,89 In 13 studies, participants experienced rejection from the social environment.…”
Section: Resultsmentioning
confidence: 99%
“…16,17,1921,3335,37,39,41,42,44,47,48,53,56,57,60,73,76,88 In 16 studies blaming from others was the second most common social stigma reported due to being infected with COVID-19. 22,23,39,40,46,48,5155,60,62,72,83,89 In 13 studies, participants experienced rejection from the social environment. 29,33,37,44,46,47,50,56,60,73,76,80,83 Other stigmas experienced by COVID-19 patients included psychological pressure, 62,6672,75,79,81 verbal violence, 20,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations